The Incorporation of an Advanced Donation Program Into Kidney Paired Exchange: Initial Experience of the National Kidney Registry. Issue 10 (26th May 2015) - Flechner, S. M.; Leeser, D.; Pelletier, R.; Morgievich, M.; Miller, K.; Thompson, L.; McGuire, S.; Sinacore, J.; Hil, G.
<x xml:space="preserve">Abstract</x> The continued growth of kidney paired donation (KPD) to facilitate transplantation for otherwise incompatible or suboptimal living kidney donors and recipients has depended on a balance between the logistics required for patients and the collaborating transplant centers. The formation of chains for KPD and the shipping of kidneys have permitted networks such as the National Kidney Registry (NKR) to offer KPD to patients over a transcontinental area. However, over the last 3 years, we have encountered patient requests for a more flexible experience in KPD to meet their individual needs often due to rigid time constraints. To accommodate these requests, we have developed an Advanced Donation Program (ADP) in which the donor desires to donate by a specific date, but their paired recipient has not yet been matched to a specific donor or scheduled for surgery. After obtaining careful informed consent from both the donor and paired recipient, 10 KPD chains were constructed using an ADP donor. These 10 ADP donors have facilitated 47 transplants, and thus far eight of their paired recipients have received a kidney within a mean of 178 (range 10–562) days. The ADP is a viable method to support time limited donors in a KPD network.